(untitled) (Zaporizhzhia Historical Review, 2021)
In article the concept of social mobility, its types and characteristics are analyzed. The author regards evolution of scientific judgement of social movings and the basic conclusions to which scientists of different generations concerning character of mobility have come, dependences and interconditionalities of different factors which define a direction and intensity of mobility. Theoretically-empirical researches of social mobility in Ukraine and the basic tendencies revealed during the analysis between generations of social mobility are described.